Effect of heat treatment on small scale fragmentation of aluminium alloy - Edwards, Michael R.; Deal, C (Maney Publishing, 2011)
Small scale explosions, using a detonator, of 7075 aluminium alloy cylinders, 15-100 mm outside diameter, were carried out to investigate the effects of heat treatment on fragmentation. This was the finest for the strongest as received alloy and coarsest for the softest overaged alloy. This effect was similar to that seen in investigations of the fragmentation of steel. Cylinders of 50 and 100 mm in diameter did not fragment but plastically deformed with maximum deformation at the cylinder bottom. Fragmentation of 33 and 42 mm diameter cylinders produced long fragments typical of the break-up of thick walled cylinders. At smaller diameters, break-up gave fragments of several shapes, finer fragments being largely associated with the smallest diameter cylinders and the highest strength alloys. Results followed those seen in large scale studies of cylinder break-up and suggest the possibility of using small scale fragmentation experiments in the investigation of the effects of composition, heat treatment and processing on natural fragmentation.
Keywords: Fragmentation Aluminium alloy Heat treatment dynamic fragmentation metals strain